The representation of homosexuals in Arabic-language news outlets - Al-Abbas, Linda S; Haider, Ahmad S (Equality, Diversity and Inclusion: An International Journal, 2021)
PurposeThe purpose of this study is to examine the most frequent countries and prevalent discourses in the context of homosexuality in the headlines of Arabic-language media outlets.Design/methodology/approachThis study combined both corpus linguistic (CL) quantitative and critical discourse analysis (CDA) qualitative approaches to analyse five thousand two hundred news headlines that were retrieved from the Factiva news database from 2010 to 2019.FindingsThere were six main categories of subjects covered by the media in the context of homosexuality, namely crime, extremist groups, legislation, authority figures and scandals, culture and countries. The analysis showed that the countries whose laws criminalize homosexuals were more frequent than those seen to be supportive of homosexuals. The findings revealed that homosexuals are under-covered in the Arab media, and whenever they are present in the news reports, they are depicted negatively.Research limitations/implicationsThis study examined the representation of homosexuals in Arabic headlines from 2010 to 2019. Future researchers may investigate their construction in the body of the articles in different periods and languages.Practical implicationsThe present research has implications regarding the necessity of objectivity in covering news about minority groups without being influenced by the stock of ideas circulating in the culture where media outlets report.Social implicationsThe social implications include enhancing the principles and values of solidarity and respecting all groups in society.Originality/valueAlthough there is considerable literature on the representation of homosexuals in media outlets, the number of articles that investigated the same concept in the Arab region is relatively limited to the best knowledge of the researchers. Therefore, this study can add great significance to existing knowledge as it tackles a limitedly investigated topic in the Arab world.